2022
DOI: 10.7759/cureus.26330
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing With the Electronic Health Record (EHR): A Comparative Review of Modes of Documentation

Abstract: Electronic health records (EHRs) have provided physicians with a systematic framework for collecting patient data, organizing notes from the healthcare team, and managing the daily workflow in the modern era of healthcare. Despite these advantages, EHRs have proven to be problematic for clinicians. The burdensome regulations requiring increased documentation with the EHR paradigm have led to inefficiencies from dataentry requirements forcing physicians to spend an inordinate amount of time on it, affecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A comparative review from 2022 compiled data on medical documentation evolution and found that custom-built templates within the EHR system not only improved overall efficiency of patients seen per hour but also the quality of the documentation and patient satisfaction 11 . EHR systems can also provide easy access to patient information quickly, perhaps increasing the overall time spent with the patient and reducing duplicate tests and questions 10 .…”
Section: Benefitsmentioning
confidence: 99%
“…A comparative review from 2022 compiled data on medical documentation evolution and found that custom-built templates within the EHR system not only improved overall efficiency of patients seen per hour but also the quality of the documentation and patient satisfaction 11 . EHR systems can also provide easy access to patient information quickly, perhaps increasing the overall time spent with the patient and reducing duplicate tests and questions 10 .…”
Section: Benefitsmentioning
confidence: 99%
“…Furthermore, novel software to reduce EHR burden will increase quality time spent in patient care and improve overall satisfaction. While integration of basic AI in clinical practices has begun, innovation has taken simple voice recognition software to clinic rooms with full voice-driven encounters, converted medical scribes to digital scribes, and added EHR templates to software, which can prepopulate entire visit notes and arrange a follow-up testing (4). These advances using AI are likely to make the greatest positive impact on day-to-day clinical practice.…”
Section: The Roadmap Of Innovation In Gastroenterologymentioning
confidence: 99%
“…This can be accomplished through the provision of information (Mehta, 2022). The ability of electronic nursing documentation to aid healthcare providers in being more productive and cost-effective is an additional significant advantage of this form of documentation (Avendano et al, 2022). The use of electronic nursing documentation comes with a number of benefits, this being one of them.…”
Section: Abudalbouh L a (2023) Electronic Nursing Documentation Inter...mentioning
confidence: 99%